State Financial Losses as a Result of Environmental Damage - Sari, Retno Dewi Pulung; Nurjaya, I Nyoman; Puspitawati, Dhiana; Monteiro, Sequito (Journal of Human Rights, Culture and Legal System, 2024)
Indeed, corporations serve as the primary consumers of resources and the primary contributors to environmental damage. Indonesia incurs substantial economic losses as a consequence of environmental damage. Corruption frequently contributes to the deterioration of these conditions, resulting in fiscal ramifications for the government that are attributable to environmental damage. This study aims to examine the state financial losses incurred by states as a result of environmental damage. This is normative-jurisprudential research. This research shows that environmental damage ultimately results in a financial loss for the state and must be recouped by the violating corporation. The deterioration of this circumstance is frequently correlated with corruption, leading to financial losses for the government due to environmental damage. Therefore, a comprehensive legal framework is required to maximize the recovery of this damage. Enhancing regulatory transparency concerning the distribution of state funds and calculating losses will ensure the legal validity of efforts to enforce environmental legislation in response to corporate violations. Furthermore, environmental damage affects the populace's well-being, resulting in economic and health repercussions and reduced state revenue. To promote sustainability, the government must regulate financial impacts through education and a greater focus on MSME business lines.